GEOCHEMICAL PRECONDITIONS OF HYDROCARBONGENESIS IN METAMORPHIC COMPLEXES OF THE MARMAROSH MASSIF (WITH FLUID INCLUSIONS) - Naumko, I.; Bondar, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of research of volatile of fluid inclusions in rock-ore complexes of different age of the north-western part of the Marmarosh massif are represented. A possibility of the formation of hydrocarbon compounds under the conditions of amphibolite and greenschists facies of metamorphism is shown. It is emphasized importance of the carbonaceous compounds in the formation and accumulation of hydrocarbons within metamorphic complexes of massif.